2020
DOI: 10.1177/1076029620945792
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Decision-Making of Secondary Prevention After Venous Thromboembolism: Data From the Real-Life START2-POST-VTE Register

Abstract: Patients with venous thromboembolism (VTE) should receive a decision on the duration of anticoagulant treatment (AT) that is often not easy to make. Sixteen Italian clinical centers included patients with recent VTE in the START2-POST-VTE register and reported the decisions taken on duration of AT in each patient and the reasons for them. At the moment of this report, 472 (66.9%) of the 705 patients included in the registry were told to stop AT in 59.3% and to extend it in 40.7% of patients. Anticoagulant trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
2
8
1
Order By: Relevance
“…This appears to be in contrast with what suggested by experts [ 2 ] and international guidelines [ 1 ] which have recommended at least 3 months of anticoagulation for all VTE patients and to consider extension of treatment in those with unprovoked events who have a non-high risk of bleeding. However, this result, fully consistent with what Italian vascular doctors decided in a cohort of VTE patients [ 12 ], indicates that many physicians in the everyday clinical practice of different countries prefer not to comply with a pretended obligation dictated by the classification as unprovoked/provoked event, but rather to try and assess the multifactorial individual recurrence risk. Indeed, at the multivariable analysis, the provoked/unprovoked nature of the event along with its site (PE or not), the presence of PTS signs and the presence of concomitant diseases, significantly affected the probability to continue with anticoagulation or antithrombotic treatment, rather than stopping.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This appears to be in contrast with what suggested by experts [ 2 ] and international guidelines [ 1 ] which have recommended at least 3 months of anticoagulation for all VTE patients and to consider extension of treatment in those with unprovoked events who have a non-high risk of bleeding. However, this result, fully consistent with what Italian vascular doctors decided in a cohort of VTE patients [ 12 ], indicates that many physicians in the everyday clinical practice of different countries prefer not to comply with a pretended obligation dictated by the classification as unprovoked/provoked event, but rather to try and assess the multifactorial individual recurrence risk. Indeed, at the multivariable analysis, the provoked/unprovoked nature of the event along with its site (PE or not), the presence of PTS signs and the presence of concomitant diseases, significantly affected the probability to continue with anticoagulation or antithrombotic treatment, rather than stopping.…”
Section: Discussionsupporting
confidence: 69%
“…Not many studies have assessed the treatment of VTE patients in real-world populations. Among Italian VTE patients, prevalently managed by vascular doctors, an anticoagulation for < 3 months was recorded in more patients (9%) than found in the present study; conversely, quite similar (36.8%) was the prevalence of patients who were treated for > 180 days [12]. Completely different results were reported in a Canadian study [13], in which only 73% of patients with proven VTE were treated with anticoagulation (with VKAs) and for a much shorter period (median 61 days).…”
Section: Discussioncontrasting
confidence: 57%
“…The introduction of DOACs, like rivaroxaban, have provided some promising results for a non-inferior, more convenient alternative anticoagulant regimen to prevent recurrent VTE. In a multicenter prospective registry study done by Antonucci et al in 2020, the most frequently prescribed treatment for extended treatment (anticoagulation therapy greater than six months up to a year) were apixaban 33.8% (5mg BID), rivaroxaban 29.3% (20mg OID), apixaban 13.1% (2.5mg BID), edoxaban 12.6% (60mg OID), LMWH/fondaparinux 6.5%, VKA 3.0%, dabigatran 1.5% (150mg BID); this study also suggests that physicians are aware of and are more comfortable with DOACs and administer them in extended anticoagulant treatment to reduce recurrent VTEs [ 38 ]. Rivaroxaban is the most studied of the DOAC drugs.…”
Section: Reviewmentioning
confidence: 58%
“…The common factors physicians used for corroborating a 12 month or indefinite anticoagulant treatment decision were age (older than 65 years), an unprovoked causal factor, proximal VTE over distal and recurrent VTE or residual thrombus [ 10 , 38 ]. Few studies included the use of D-dimer level monitoring in conjunction, and results were similar to those who did not, suggesting D-dimer may not provide pertinent evidence in the decision-making process [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…12,13,18 The frequency of PE in our study (64%) was markedly higher than the previously reported in real-world VTE studies, where it ranges from 25% to 38%. 19,20 In the previously mentioned RIETE Registry study, 83% of COVID-19 patients with VTE had acute PE, while only 17% had isolated DVT. 17 A meta-analysis that included COVID-19…”
Section: F I G U R E 1 Kaplan-meier Curve For Mortality and Major Bleeding [Colour Figure Can Be Viewed At Wileyonlinelibrarycom]mentioning
confidence: 99%